PENGANTIN TAMAT KAJI SEBAGAI TRADISI PADA UPACARA PERNIKAHAN MASYARAKAT BATANG ASAI DALAM SOROTAN LIVING QUR’AN - Nugroho, Bambang Husni; Mustaniruddin, Ahmad; Surbakti, Junita BR. (TAJDID: Jurnal Ilmu Ushuluddin, 2022)
Traditions inherited from ancestors from generation to generation always have a deep moral message. In addition, the process of preserving local culture has also experienced a pattern of integration of religious teachings, especially Islam. The tradition of ending kaji is a unique tradition rooted in the people of Muara Pemuat Batang Asai Village as a form of local culture that has integrated Islamic teachings. Because of this, this research aims to uncover the messages contained in the tradition of the end of the study by focusing on knowing the basis, procession, meaning, understanding and values contained in this tradition. To dig up all the necessary information, this field-based research uses qualitative methods by applying the meaning approach and the living Qur'an approach. Like the field qualitative method, in collecting research data using observation, documentation and in-depth interviews. This study found that the implementation of the tradition of the kaji graduate, apart from being based on the hereditary habits of the ancestors, was also reinforced by various arguments about the virtues of reading the Koran. The procession in this tradition is generally divided into two, namely the process of picking up the bride and groom by the main bako (bibik) to take her home, and the process of sending her back to the parents' house after being decorated and ready to carry out the end of the study. Uniquely when picking up, the bako mother has to carry a peliman, which is a bowl containing lime, betel nut, areca nut, and a knife or keris left by the ancestors. Then when sending back, the bride and groom are taken to the parents' house to be honored by asang-asung, a chair tied with bamboo and decorated which has been lifted by the relatives of ipa (cousins), and the main bako accompanies from behind carrying the main paibut, jamba, and rice tray. For the people of Muara Pemuat village, the end of the study tradition is understood in terms of its functions and benefits. The function of this tradition is as a token of parental gratitude, as a form of parental responsibility towards their children, and as a reinforcement of local customs. Then the benefits that can be drawn from this tradition are to obtain blessings, to become a means of increasing reading of the Qur'an, to motivate families about the importance of being proficient in reading the Qur'an, to become a place for friendship, to become a place for self-maturity and finally, to become a means of charity. Not only that, the tradition of graduating from the study also contains deep values. There are at least eight values contained in this tradition, namely divine values, human values, spiritual values, ritual values, life values, social values, moral values and intellectual values Tradisi warisan para leluhur dari generasi ke generasi senantiasa memiliki pesan moral yang mendalam. Selain itu proses pelestarian budaya lokal juga telah mengalami pola integrasi ajaran keagamaan terutama agama Islam. Tradisi tamat kaji adalah tradisi unik yang mengakar pada masyarakat Desa Muara Pemuat Batang Asai sebagai bentuk budaya lokal yang telah terintegrasi ajaran agama Islam. Sebab itu penelitian ini bertujuan untuk menyingkap pesan yang terkandung dalam tradisi tamat kaji dengan berfokus pada mengetahui tentang dasar, prosesi, pemaknaan, pemahaman hingga nilai-nilai yang terkandung dalam tradisi tersebut. Untuk menggali semua informasi yang diperlukan, penelitian yang berbasis lapangan ini menggunakan metode kualitatif dengan menerapkan pendekatan makna dan pendekatan living Qur’an. Layaknya metode kualitatif lapangan, dalam mengumpulkan data penelitian ini menggunakan metode observasi, dokumentasi dan wawancara mendalam. Penelitian ini menemukan bahwa pelaksanaan tradisi tamat kaji, selain didasari oleh kebiasaan turun temurun nenek moyang, juga diperkuat oleh berbagai dalil tentang keutamaan tentang membaca al-Qur’an. Prosesi dalam tradisi inipun secara umum terbagi dua yaitu proses penjemputan pengantin oleh induk bako (bibik) untuk dibawa kerumahnya, dan proses pengantaran kembali ke rumah orangtua setelah selesai dihias dan siap melaksanakan tamat kaji. Uniknya saat penjemputan, induk bako harus menggendong peliman yaitu sebuah mangkuk yang berisi kapur, sirih, pinang, dan pisau atau keris peninggalan nenek moyang. Kemudian saat pengantaran kembali, pengantin dibawa ke rumah orang tua dengan dijunjung asang-asung, sebuah kursi yang diikat dengan bambu dan sudah diberi dekorasi yang diangkat oleh para sanak ipa (sepupu), dan induk bako mengiring dari belakang dengan membawa induk paibut, jamba, dan talam beras. Bagi masyarakat desa Muara Pemuat tradisi tamat kaji ini dipahami dari segi fungsi dan manfaatnya. Fungsi dari tradisi ini yaitu sebagai tanda terima kasih orangtua, sebagai bentuk tanggung jawab orangtua terhadap anaknya, dan sebagai penguatan adat istiadat setempat. Kemudian manfaat yang dapat diambil dari tradisi ini yaitu untuk memperoleh keberkahan, menjadi sarana peningkatan baca al-Qur’an, memotivasi keluarga betapa tentang pentingnya mahir membaca al-Qur’an, menjadi ajang silaturrahmi, menjadi ajang pendewasaan diri dan terakhir menjadi sarana bersedekah. Tidak hanya sebatas itu, tradisi tamat kaji ini juga memiliki kandungan nilai yang dalam. Setidaknya ada delapan nilai yang terkandung dalam tradisi ini yaitu nilai ketuhanan, nilai kemanusiaan, nilai spiritual, nilai ritual, nilai kehidupan, nilai sosial, nilai moral dan nilai intelektual